Finite-Time Stabilization for p-Norm Stochastic Nonlinear Systems with Output Constraints - Shijun Guan; Liandi Fang (Complexity)
This paper investigates the finite-time stability problem of p-norm stochastic nonlinear systems subject to output constraint. To cope with the constraint on system output, a tan-type barrier Lyapunov function (BLF) is constructed. By using the constructed BLF and the backstepping technique, a new control algorithm is proposed with a continuous state-feedback controller being designed, which guarantees not only that the requirement of output constraint is always achieved but also that the origin of the system is finite-time stable. This result is demonstrated by both the rigorous analysis and the simulation example.